Fabrication of Bio-MEMS Nanostructure by focused ion beam - Ali, Mohammad Yeakub; Mohd Fuad, Nurul Hajar (2010)
This work investigated the influence of two FIB process parameters, (i) acceleration voltage, (ii) dwell time with respect to milled depth. The response variable was average surface roughness (Ra). Statistical models of responses were developed using Taguchi method of design of experiment. Signal to noise ratio were calculated and analyzed for all of the responses. Developed models were used for multiple response optimizations by desirability function approach to obtain minimum Ra. The optimized values of Ra were 13.7 nm was obtained at acceleration voltage of 20 keV, dwell time of 15 μs and milled depth of 0.6 μm. By using these process parameters, microfeatures such as microholes, micro/nano pillars and etc. were fabricated.